Estudo teórico da reação de flavonoides com o radical livre DPPH - Maciel, Eduardo Nunes (2013)
The free radicals are reactive molecules due to the presence of one or more electron(s) unpaired(s). The formation of these free radicals in our body are related to various kinds of disorders and diseases. A very important group of substances in fighting free radicals is the flavonoids. Molecular modeling is a powerful tool to simulate chemical reactions providing important data about these reactions. The aim of this study was to simulate the reactions, the transfer mechanism hydrogen atom, between flavonoids 3-hydroxyflavone, morin, quercetin, fisetin and kaempferol with the free radical DPPH, using density functional theory. With the values of free energy of activation, calculations on the rates of forward and reverse reactions for every attack on each flavonoids' hydroxyl group were performed. With the values of variation in the free energy of the reactions obtained for each attack, it was discussed the efficiency in fighting free radicals. of each flavonoid when reacting with DPPH. The results showed that the flavonoid morin, by the reaction of hydroxyl 2', was presented the lowest variation free energy of reaction. The reaction occurred with a lower free energy of activation by fisetin was the reaction of their hydroxyl in position 3. For flavonoids studied, the lowest values of free energy change of reaction were found to attacks of the B ring hydroxyls, especially when the flavonoid presented catechol group in its structure. In general, the theoretical study of the reactions of flavonoids with DPPH was more complete in relation to the data described in the literature, as well as the values of free energies of reaction, we obtained the structures of transition states as well as the values of free energy of activation for the type of mechanism study.